Novel 4(3H)-quinazolinones containing biologically active thiazole, pyridinone and chromene of expected antitumor and antifungal activities - El-Bayouki, Khairy Abdel Hameed Mohsen; Basyouni, Wahid Mohamed; Mohamed, Yahia Abdel Fatah; Aly, Mohsen Mohamed; Abbas, Samir Youssef (European Journal of Chemistry, 2011)
Novel 4(3H)-quinazolinone derivatives with biologically active moieties were synthesized. Reactions of 2-cyano-N-(6-iodo-2-methyl-4-oxoquinazolin-3(4H)-yl) acetamide with carbon disulfide, isothiocyanates followed by cycloalkylation afforded acrylamide, 1,3-dithiazole, 1,3-dithiane, thiazole and pyrazole derivatives. The 2-pyridone derivatives were obtained via reaction of cyanoacetamide with some acetylacetone or arylidenes. Cyclocondensation reaction of cyanoacetamide with o-hydroxy aldehydes furnished chromene derivatives. Screening for some selected compounds was carried for their potential antitumor and antifungal activities. 2-Cyano-N-(6-iodo-2-methyl-4-oxoquinazolin-3(4H)-yl)-2-(4-methyl-3-phenyl-thiazol-2(3H)ylidene)-acetamide with 3-side chain incorporated with substituted thiazole moiety was found to be of high to moderate activity towards cells. Also, the latter product showed high activity against Aspergillus ochraceus Wilhelm with inhibition zone (18 mm) compared with (20 mm) Nystatin inhibition zone.